Increased newborn NICU admission for evaluation of hypoxic-ischemic encephalopathy during COVID-19 pandemic in a public hospital - Song, Dongli; Narasimhan, Sudha Rani; Huang, Angela; Jegatheesan, Priya (Frontiers in Pediatrics, 2023)
Background. Prenatal and perinatal care of pregnant mothers has been adversely affected during the COVID-19 pandemic. Hypoxic-ischemic encephalopathy (HIE) is a leading cause of neonatal death and long-term neurological disabilities. Therapeutic hypothermia is effective for neonatal HIE. This study evaluated the effect of the pandemic on neonatal HIE. Methods. This retrospective single-center study compared neonatal HIE evaluation and hypothermia treatment between pre-COVID-19 pandemic (January 1, 2018, to December 31, 2019) and COVID-19 pandemic (January 1, 2020, to December 31, 2021) periods. Infants with abnormal neurological examination and or significant metabolic acidosis were admitted to NICU for evaluation of HIE and therapeutic hypothermia. Demographics, NICU admission and interventions, and neonatal outcomes were compared between infants born during the two periods using chi-square, t-test, and Wilcoxon rank-sum test as appropriate. Statistical Process Control charts show the yearly proportion of infants evaluated for HIE and those treated with therapeutic hypothermia. Results. From the pre-pandemic to the pandemic period, the proportion of infants that met HIE screening criteria increased from 13% to 16% (p<0.0001), the proportion of infants admitted to NICU for HIE evaluation increased from 1% to 1.4% (p=0.02), and the maternal hypertension rates of the admitted infants increased from 30% to 55% (p=0.006). There was no difference in the proportions of the infants diagnosed with HIE (0.7% vs. 0.9%, p=0.3) or treated with therapeutic hypothermia (0.2% vs. 0.3%, p=0.3) between the two periods. There were no differences in the HIE severity and outcomes of the infants treated with therapeutic hypothermia between the two periods. Conclusion. During the COVID-19 pandemic, we observed a significant increase in NICU admission for HIE evaluation. While we did not find significant increases in neonatal HIE and the need for therapeutic hypothermia, larger studies are needed for a comprehensive assessment of the impact of the COVID-19 pandemic on neonatal HIE.